STYLISTIKA RELASI GENDER BADAN EKSEKUTIF MAHASISWA IAIN AMBON - Arman Arfa (Al-Qalam, 2010)
This research focuses on the pattern of gender relation in Student Executive Organization of IAIN Ambon. The problem addressed by thisresearch was: what is student perception on gender relation and what the pattern ofgender relation in Student Executive Organization ofIAIN Ambon.The objective of this research is to find out student perception on gender and gender relation in Student Executive Organization ofIAINAmbon. Research promotes the understanding of students on gender and the role of woman in public domain.Research is qualitative. Data collected through in depth interview to the member of Student Executive Organization of IAIN Ambon,observing their activity andfinding out information in current documents.Result shows that samples have some general perception about gender relation; for them, gender means biological difference and equalrights, men can do what women do, and women can do what men do. Three patterns ofgender relation were found in Student ExecutiveOrganization of IAIN Ambon: woman cannot become a leader, man is much appropriate to be a leader and man and woman have thesame opportunity to be the leader, particularly for Student Executive Organization ofIAIN Ambon